2021
DOI: 10.1021/acsomega.1c05620
|View full text |Cite
|
Sign up to set email alerts
|

Phase Relations in the Na, K//Cl, SO4, CO3–H2O Quinary System at 35 °C

Abstract: The phase equilibria in the quinary Na, K//Cl, SO 4 , CO 3 –H 2 O system at 35 °C were determined, and a total phase equilibria diagram of the system was constructed by means of the translation method. Six points saturated with four solid phases, 19 curves saturated with three solid phases, and 21 fields saturated with two solid phases were determined in the system. Structures of dry-salt diagrams for the parts saturated with each of the nine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Through the phase equilibria of the salt-water system, the dissolution and crystallization behavior of salts in solution can be obtained. Accordingly, a series of phase equilibria studies have been done aimed at different types of brine. As for the main components of the Pingluo brine, they can be simplified as the Li + , Na + , K + , Rb + , Mg 2+ //Cl – , Borate-H 2 O system. Therefore, to understand the thermodynamic behaviors of the complex system, phase diagrams of some subsystems have been measured. For the borate-containing system, the crystalline form of boron appears in many polymeric forms such as BO 2 – , B­(OH) 4 – , B­(OH) 3 , B 4 O 7 2– , and B 5 O 8 – when the coexisting ions and temperature change. , As for the quinary system Li + , K + , Rb + //Cl – , Borate-H 2 O at 323.2 K, the corresponding nine ternary subsystems and five quaternary subsystems at 323.2 K have been studied. The research results show that two boron species, B 4 O 7 2– and B 5 O 8 – , were found in the borate system containing potassium/lithium and rubidium; the solid solution [(K, Rb)­Cl] was formed in the chloride type system containing potassium and rubidium; and the rubidium carnallite RbCl·MgCl 2 ·6H 2 O was found in the chloride type system containing magnesium and rubidium.…”
Section: Introductionmentioning
confidence: 99%
“…Through the phase equilibria of the salt-water system, the dissolution and crystallization behavior of salts in solution can be obtained. Accordingly, a series of phase equilibria studies have been done aimed at different types of brine. As for the main components of the Pingluo brine, they can be simplified as the Li + , Na + , K + , Rb + , Mg 2+ //Cl – , Borate-H 2 O system. Therefore, to understand the thermodynamic behaviors of the complex system, phase diagrams of some subsystems have been measured. For the borate-containing system, the crystalline form of boron appears in many polymeric forms such as BO 2 – , B­(OH) 4 – , B­(OH) 3 , B 4 O 7 2– , and B 5 O 8 – when the coexisting ions and temperature change. , As for the quinary system Li + , K + , Rb + //Cl – , Borate-H 2 O at 323.2 K, the corresponding nine ternary subsystems and five quaternary subsystems at 323.2 K have been studied. The research results show that two boron species, B 4 O 7 2– and B 5 O 8 – , were found in the borate system containing potassium/lithium and rubidium; the solid solution [(K, Rb)­Cl] was formed in the chloride type system containing potassium and rubidium; and the rubidium carnallite RbCl·MgCl 2 ·6H 2 O was found in the chloride type system containing magnesium and rubidium.…”
Section: Introductionmentioning
confidence: 99%